Foreign Currency Transaction, Translation and Performance of Supernational Companies in Nigeria, West Africa - Osho, Augustine; OLUFEMI, IBIFUNMILOLA David (Annals of Spiru Haret University. Economic Series, 2022)
The study examined foreign currency transaction, translation and performance of supernational companies in Nigeria. Specifically, the study examined effect of exchange rate, transaction rate and interest rate on return on asset of supernational companies in Nigeria. In a bid to accomplish this, panel regression analysis of fixed and random effect on five (5) selected supranational companies in Nigeria were employed. The study employed secondary data; the data for the study cover the period 2012 to 2021. The Hausman test carried out showed that fixed effect model is more realistic and produced a better result which was therefore employed in drawing inferences in the study. From the result, exchange rate exhibited significant negative relationship with supernational company’s performance in Nigeria. The finding further revealed that Interest rate has insignificant positive relationship with performance of the supernational companies in Nigeria while the translation rate indicated insignificant negative relationship. Hence, the study concluded that unfavourable movement or adjustment in foreign currency transaction and translation rate affect the performance of supernational companies in Nigeria, especially, when measured performance in term of return on asset. It was recommended that supernational companies should develop a mechanism to hedge against foreign exchange rate exposure caused by unanticipated movement in the exchange rate. More so, this should be supported by sound risk management strategies that can withstand macroeconomic instability especially inflation rate in the host economy.